2017
DOI: 10.1002/ange.201611509
|View full text |Cite
|
Sign up to set email alerts
|

The Lightest Element Phosphoranylidene: NHC‐Supported Cyclic Borylidene–Phosphorane with Significant B=P Character

Abstract: A borylidene–phosphorane, the lightest phosphoranylidene, which is stabilized by an N‐heterocyclic carbene ligand, was synthesized and fully characterized. Experimental electron density analysis and DFT calculations indicate an enhanced ylene character (rather than an ylide character) with an exceptionally strong B→P π‐back bonding related to the less electronegative boron compared to phosphorus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 91 publications
2
12
0
Order By: Relevance
“…[12] Since the first isolation of ab orylene stabilized by two cyclic alkyl-amino carbenes (cAAC) VII by Bertrand et al, [13] several stable borylene complexes with different ligands have been described VIII, IX. [16,17] Of particular interest, these boron species,b eing isoelectronic with amines,p resent an ucleophilic three-coordinate boron center with al one-pair, [13,14] and it has been clearly demonstrated that they can be used as s-donating ligands for transition metals. [16,17] Of particular interest, these boron species,b eing isoelectronic with amines,p resent an ucleophilic three-coordinate boron center with al one-pair, [13,14] and it has been clearly demonstrated that they can be used as s-donating ligands for transition metals.…”
mentioning
confidence: 99%
“…[12] Since the first isolation of ab orylene stabilized by two cyclic alkyl-amino carbenes (cAAC) VII by Bertrand et al, [13] several stable borylene complexes with different ligands have been described VIII, IX. [16,17] Of particular interest, these boron species,b eing isoelectronic with amines,p resent an ucleophilic three-coordinate boron center with al one-pair, [13,14] and it has been clearly demonstrated that they can be used as s-donating ligands for transition metals. [16,17] Of particular interest, these boron species,b eing isoelectronic with amines,p resent an ucleophilic three-coordinate boron center with al one-pair, [13,14] and it has been clearly demonstrated that they can be used as s-donating ligands for transition metals.…”
mentioning
confidence: 99%
“…[26] These results clearly demonstrate the remaining silanone character of 2 despite its significant electronic perturbation by the strongly electrondonating amino and phosphonium bora-ylide substituents. Therefore,t he Si1ÀO1 and PÀBbond lengths are elongated and the Si1ÀBbond length is shorten (Si1ÀO1 1.553 ,P ÀB1 .852 ,S i1ÀB1 .865 ) relative to those observed for 2 (Si1 À O1 1.5432 (12) ,B À P 1.8175 (16) ,S i1 À B1 .8985 (15) ;F igure 5, left). Although no significant NMR data differences were observed between 8 ( 29 Si NMR:7 0.9 and 77.7 ppm, 11 (3);C 1-P1-B1 133.15 (15),N 2-P1- C11 14.29(14), N2-P1-B1 110.32- (14).…”
Section: Angewandte Chemiementioning
confidence: 92%
“…[6] Recently,e asy-to-handle silanones stabilized as donor-acceptor or donor complexes,h ave been reported. Herein we report that the introduction of as trongly donating phosphonium boraylide substituent considerably extends the lifetime of silanone 2 (t 1/2 = 4days,a tR T), which allows easier manipulation to study its properties and reactivity.Recently,w eh ave described that the electropositive boron-based substituent (phosphonium bora-ylide), [16,17] with an exceptionally strong electron donating character,i s able to efficiently stabilize highly reactive species such as Nheterocyclic silylene 1,the related silylium ion and transitionmetal-silylene complexes featuring at rigonal-planar geometry around the silicon center. [15] Therefore,t heir synthetic use is still limited because of the scarcity and limited lifetime (0.5-5 h, at RT for VI).…”
mentioning
confidence: 99%
See 2 more Smart Citations